The vertical structure of Jupiter's equatorial zonal wind above the cloud deck, derived using mesoscale gravity waves. Issue 3 (13th February 2013) - Watkins, C.; Cho, J. Y‐K.
<x xml:space="preserve">Abstract</x> [1] Data from the Galileo Probe, collected during its descent into Jupiter's atmosphere, is used to obtain a vertical profile of the zonal wind from 0.5 bar (upper troposphere) to 0.1 µbar (lower thermosphere) at the probe entry site. This is accomplished by constructing a map of gravity wave Lomb‐Scargle periodograms as a function of altitude. The profile obtained from the map indicates that the wind speed above the visible cloud deck increases with height to 150 m s‐1 and then levels off at this value over a broad altitude range. The location of the turbopause, as a region of wide wave spectrum, is also identified from the map. In addition, a cross‐equatorial oscillation of a jet, which has previously been linked to the QQO in the stratosphere, is suggested by the profile.